ISSUES OF EXPLAINING TO STUDENTS OF VOCATIONAL EDUCATION INSTITUTIONS THE IMPORTANCE OF MATHEMATICS NOT ONLY AS A DEDUCTIVE SCIENCE, BUT ALSO FOR CREATIVE AND SCIENTIFIC WORK (Modern education and development, 2025)
The article discusses events in the field of professional education in Uzbekistan. In the professional educational institution, it was also discussed that mathematics is not only a deductive science, but also an important tool for creative and scientific work.